How many species of Pleurothallidinae are there? - Pupulin, Franco (2019)
Subtribe Pleurothallidinae is possibly the most species-rich of all orchid groups. Nevertheless, they are a young group of plants in terms of scientific learning. The last three decades have been the most active with respect to taxonomic and systematic studies within the group, contributing an increasing rate of new taxa in the subtribe. Can a reasonable estimation of the real diversity of Pleurothallidinae be made at this time? We addressed the question through an analysis of the partial results of a 15-year study of the pleurothallid flora of Costa Rica. We summarized the main historical stages of the discovery of Pleurothallidinae richness and show how much it has changed our understanding of diversity as a consequence of more focused research. In 15 years the number of Pleurothallidinae increased from 433 species to 561 species (+30%). New taxa have been described in most of the pleurothallid genera recorded from Costa Rica, including Acianthera, Anathallis, Brachionidium, Dracula, Dresslerella, Echinosepala, Lepanthes, Masdevallia, Myoxanthus, Octomeria, Pabstiella, Platystele, Pleurothallis, Restrepiella, Trichosalpinx, Trisetella, Specklinia, and Stelis. The largest pleurothallid genera in Costa Rica are Lepanthes (with 150 species so far), Stelis (106 species), and Pleurothallis s.s. (51 species), three genera that we have not yet fully monographed. Projecting the trend observed in the genera and groups studied in more detail and mapping the collection effort carried out in Costa Rica, a further 300 new species of Pleurothallidinae could be expected. We can now estimate with some confidence that the total number of Pleurothallidinae for the flora of Costa Rica would exceed 800 species, and this means that roughly 2 of every 5 orchid species recorded in the country will be a pleurothallid. An updated checklist of Pleurothallidinae accepted for the flora of Costa Rica is presented, including 561 species in 30 genera. A new name and two new combinations are proposed in Stelis.